The role user’s interface of the decision to purchase accommodation in Bali on the traveloka.com site - I Gusti Agung Gede Witarsana; I Gusti Ayu Putu Wita Indrayani; I Kadek Arisanjaya (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The development of Traveloka.com as a Online Travel Agents in Indonesia provides an easier access to customer. In Traveloka.com’s user interface, there are some indicators namely, brand image, price, online reviews, and location. This research aims to determine the effect of brand image, price perception, online reviews, and location on the decision to purchase an accommodation in Bali through Traveloka.com. The datas research were collected by using questionnaire. This study uses quantitative descriptive analysis techniques through multiple linear regression methods, T test, F test and test the coefficient of determination (R2). Based on the results, indicated that brand image, price perceptions, online reviews, and location have a positive effect to influence customer to create an accommodation reservation in Bali through Traveloka.com site. The coefficient of determination test produces an R square value of 0.617, which means that brand image (X1), price perception (X2), online reviews (X3), and location (X4) have an effect of 61,7% on accommodation purchase decisions (Y) while the rest of 38.3% is influenced by other factors outside of the variables in this research.